Measurements and modeling of coherent synchrotron radiation and its impact on the Linac Coherent Light Source electron beam - K. L. F. Bane; F.-J. Decker; Y. Ding; D. Dowell; P. Emma; J. Frisch; Z. Huang; R. Iverson; C. Limborg-Deprey; H. Loos; H.-D. Nuhn; D. Ratner; et al. (Physical Review Special Topics. Accelerators and Beams, 2009)
In order to reach the high peak current required for an x-ray free electron laser, two separate magnetic dipole chicanes are used in the Linac Coherent Light Source accelerator to compress the electron bunch length in stages. In these bunch compressors, coherent synchrotron radiation (CSR) can be emitted either by a short electron bunch or by any longitudinal density modulation that may be on the bunch. In this paper, we report detailed measurements of the CSR-induced energy loss and transverse emittance growth in these compressors. Good agreement is found between the experimental results and multiparticle tracking studies. We also describe direct observations of CSR at optical wavelengths and compare with analytical models based on beam microbunching.